Unusual algorithms for lexicographical enumeration - Dömösi, Pál (Acta Cybernetica, 2000)
Using well-known results, we consider algorithms for finding minimal words of given length n in regular and context-free languages. We also show algorithms enumerating the words of given length n of regular and contextfree languages in lexicographical order.